Open Heart: Entering the Dynamic of Polyamorous Relationship. - Lucky Juliandino (Institute of Research and Community Outreach - Petra Christian University, 2021)
Open Heart is a screenplay under a romantic comedy drama subgenre, which recounts a romantic tale about a monogamous, lonely, single man who is struggling to accept and exercise an open heart during a novel participation in polyamory that the woman he falls for is involved with. In this project, I investigated why my protagonist join a polyamorous courtship and how he handles the common hurdles in consensually non-monogamous (CNM) experiences, specifically, jealousy and stigma-based shame. I answered these problems using findings from polyamory, romantic jealousy and Gregory M. Herek’s sexual stigma concepts. The results determine that my protagonist only agrees to polyamory out of compliance. Also, in order to solve his plights, he needs to uphold particular management for jealousy and shame. Hopefully, by showcasing these issues around non-monogamy and polyamory, I wish my story could promote a wider understanding, along with uncovering the oppression still targeting them. Keywords: Polyamory, consensual non-monogamy, CNM, romantic comedy, romantic jealousy, sexual stigma